Hmm, let me think and I'll answer it.
Answer:
Step-by-step explanation:
R = (5+T)P/3
3R = (5+T)P
3R/ (5+T) = P
Answer:
23
Step-by-step explanation:
hey
Answer:
2x^4-11x^3+68x-80
2x^4-4x^3-7x^3+14x^2-14x^2+28x+40x-80
2x^3(x-2)-7x^2(x-2)-14x(x-2)+40(x-2)
(x-2)(2x^3-7x^2-14x+40)
(x-2)(2x^3-4x^2-3x^2+6x-20x+40)
(x-2)(2x^2(x-2)-3x(x-2)-20(x-2))
(x-2)(x-2)(2x^3-3x-20)
(x-2)(x-2)(2x^2+5x-8x-20)
(x-2)(x-2)(x(2x+5)-4(2x+5))
(x-2)(x-2)(2x+5)(x-4)
(x-2)^2(2x+5)(x-4)
A) Isolate y in both inequalities
1) x + y ≥ 4 => y ≥ 4 - x
2) y < 2x - 3
B) Draw the lines for the following equalities:
1) y = 4 - x
2) y = 2x - 3
C) Shade the regions of solutions
1) The region that is over the line y = 4 - x
2) The region that is below the line y = 2x - 3
The solution is the intersection of both regions; this is the sector between both lines that is to the right of the intersection point, including the portion of the very line y = 4 - x and excluding the portion of the very line y = 2x - 3